Adopsi QRIS oleh UMKM dengan Menggunakan Theory of Interpersonal Behavior - Atahau, Apriani Dorkas Rambu; Himaya, Devi Nila (Faculty of Economics and Business Universitas Jenderal Soedirman, 2022)
The purpose of this study was to obtain empirical evidence regarding the interest of MSME actors in adopting QRIS as a digital payment with the Theory of Interpersonal Behavior (TIB) approach. The data used in this study is primary data obtained through questionnaires distributed to 100 MSME actors in Central Java using a purposive sampling method with the Slovin formula. The data analysis technique used partial regression analysis (Partial Least Square/PLS). The results of this study prove that attitudes and emotional responses have a significant positive effect on the interest of MSME actors in using QRIS as digital payments, interest has a significant positive effect on the behavior of MSME actors in using QRIS as digital payments, and repeated behavior in the past has a significant effect on the formation of positive habits. SMEs in using QRIS as digital payments. While the results in accordance with the hypothesis are that social factors do not have a significant positive effect on the interest of MSME actors in using QRIS as a digital payment, the habits and conditions that facilitate it as moderating do not significantly affect the behavior of MSME actors in using QRIS as a digital payment.